Erosión hídrica bajo tres estadios de sucesión de bosque dentro del Parque Nacional Palo Verde, Costa Rica - Rojas-Zeledón, Ignacio José (Instituto Tecnológico de Costa Rica, 2017)
Hydric erosion was studied under three forest stages of succession in Palo Verde National Park. Erosion and sedimentation rates were evaluated on three tropical dry forest stages of succession: early, intermediate, late and three slope conditions 20, 30 and 40% affected by the rain around Palo Verde lagoon in Guanacaste region, Bagaces-Costa Rica. The study area is characterized because of their clayey soils and proximity to chalky hills that overlap abruptly from sea level to 1000 m.a.s.l. approximately. It found significant differences between stages of succession, but not between the three different slope percentages. Under a maximum rain intensity average of 23 mm/15 min, the early stage succession is the highest sediment producer with an average value of 4.75 Mg/ha/year.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2017.
Keywords: Sedimentación; Suelo; Parque nacionales; Bosques; Humedales